2004
DOI: 10.1152/ajprenal.00270.2003
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression alterations during HGF-induced dedifferentiation of a renal tubular epithelial cell line (MDCK) using a novel canine DNA microarray

Abstract: Hepatocyte growth factor (HGF) elicits a broad spectrum of biological activities, including epithelial cell dedifferentiation. One of the most widely used and best-studied polarized epithelial cell lines is the Madin-Darby canine kidney (MDCK) cell line. Here, we describe and validate the early response of polarized monolayers of MDCK cells stimulated with recombinant HGF using a novel canine DNA microarray designed to query 12,473 gene sequences. In our survey, eight genes previously implicated in the HGF sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 41 publications
3
22
0
Order By: Relevance
“…The fold changes for the conditions (HGF, HGF + PD, control, and PD alone) are shown in graph form. The fold change for fibronectin following stimulation with HGF for 24 hours as determined by realtime PCR was very similar to the 4.89-fold change obtained previously by real-time PCR [23]. Inhibition of upregulation was seen with the addition of PD or UO (not shown).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The fold changes for the conditions (HGF, HGF + PD, control, and PD alone) are shown in graph form. The fold change for fibronectin following stimulation with HGF for 24 hours as determined by realtime PCR was very similar to the 4.89-fold change obtained previously by real-time PCR [23]. Inhibition of upregulation was seen with the addition of PD or UO (not shown).…”
Section: Discussionsupporting
confidence: 86%
“…For a typical real-time PCR experiment, the calculated fold increase for fibronectin, normalized to the 18S ribosome (a control mRNA), was 4.14 +/− 0.69 for 24 h of HGF exposure compared to 0 h of HGF exposure (control) ( Figure 1). This was very similar to the fold increase in fibronectin mRNA by HGF as determined by microarray analysis and real-time PCR in our previous study [23]. The increase in fibronectin mRNA expression following 24 hours of exposure to HGF was prevented by the addition of the MEK inhibitors PD (Figure 1) and UO (not shown).…”
Section: Fibronectin Activation Via the Mapk/erk Pathway Using Real-tsupporting
confidence: 89%
See 1 more Smart Citation
“…It was, therefore, not surprising to find that our dataset of differentially expressed genes was enriched in genes that encode proteins involved with cell adhesion and with the formation or remodeling of the ECM. In fact, microarray analysis of HGF-treated MDCK cells has shown that this treatment alters the expression of a large number of genes, particularly those involved in ECM associations (1,20). Additionally, an Affymetrix microarray analysis of HGF-stimulated MDCK cells revealed an upregulation of the expression of MMP13 and TIMP1 (14).…”
Section: Discussionmentioning
confidence: 99%
“…Our first step was to establish an expression profile for known calcium channels in MDCK cells by reverse transcriptase PCR. Since c-met activation triggers dramatic changes in gene expression in MDCK cells (Balkovetz et al, 2004), calcium channel expression was determined before and after HGF treatment. We found detectable levels of expression of a number of Trp calcium channels, including TrpC 1, 4, 6 and 7, TrpV 1-4, TrpM 3-8 and PKD 1-2 (Fig.…”
Section: Identification Of Channels That Participate In Hgf Signalingmentioning
confidence: 99%